Peran Manajemen Sumber Daya Manusia Dalam Mencapai Tujuan Strategis Universitas Sehati Indonesia - Dedi Sudrajat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The global transformation of higher education over the past two decades has elevated strategic human resource management (SHRM) as a critical driver of institutional competitiveness and sustainability. This study explores how SHRM practices contribute to the achievement of strategic objectives at Universitas Sehati Indonesia (USINDO) and identifies factors influencing implementation effectiveness in a private higher education context. Employing a qualitative single-case design, data were collected through in-depth interviews, document analysis, and non-participant observation. Informants included university leadership, human resource managers, deans, program heads, and faculty representatives. Thematic analysis revealed six core SHRM practices competency-based recruitment and selection, continuous training and development, performance appraisal with constructive feedback, strategic compensation, research and community engagement support, and workload management each integrated horizontally to form a coherent system aligned with the university’s Tri Dharma mission. Findings demonstrate that SHRM effectiveness is mediated by leadership commitment, a culture of innovation and collaboration, and adaptive responses to external challenges such as financial constraints and regulatory pressures. The transformation of HR into a strategic partner, as conceptualized by Ulrich, underscores its proactive role in shaping institutional strategy and securing valuable, rare, inimitable, and non-substitutable human capital. The study confirms that integrated SHRM fosters work engagement, enhances academic excellence, and drives sustainable competitive advantage despite resource limitations. Practical implications suggest that private universities should adopt holistic SHRM frameworks, strengthen leadership support, and leverage institutional branding to attract and retain talent. Future research employing mixed-methods and focusing on digitalization of HR functions and compensation models is recommended to generalize and extend these findings.